Pathogenic Variants in ABHD16A Cause a Novel Psychomotor Developmental Disorder With Spastic Paraplegia - Yahia, Ashraf; Elsayed, Liena E. O.; Valter, Remi; Hamed, Ahlam A. A.; Mohammed, Inaam N.; Elseed, Maha A.; Salih, Mustafa A.; Esteves, Typhaine; Auger, Nicolas; Abubaker, Rayan; Koko, Mahmoud; Abozar, Fatima; et al. (Frontiers in Neurology, 2021)
Introduction: Hereditary spastic paraplegia is a clinically and genetically heterogeneous neurological entity that includes more than 80 disorders which share lower limb spasticity as a common feature. Abnormalities in multiple cellular processes are implicated in their pathogenesis, including lipid metabolism; still, 40% of the patients are undiagnosed. Our goal was to identify the disease-causing variants in Sudanese families excluded for known genetic causes and describe a novel clinico-genetic entity. Methods: We studied four patients from two unrelated consanguineous Sudanese families who manifested a neurological phenotype characterized by spasticity, psychomotor developmental delay and/or regression, and intellectual impairment. We applied next-generation sequencing, bioinformatics analysis, and Sanger sequencing to identify the genetic culprit. We then explored the consequences of the identified variants in human cell lines and patients-derived fibroblasts using targeted-lipidomics strategies. Results and Discussion: Two homozygous null variants in ABHD16A segregated with the disease in the two studied families. ABHD16A encodes the main brain phosphatidylserine hydrolase. In vitro, we confirmed that ABHD16A loss of function reduces the levels of certain long-chain lysophosphatidylserine species while increases the levels of multiple phosphatidylserine species in transfected human-derived HeLa cells and patient’s fibroblasts. Conclusion: ABHD16A null variants are implicated in the pathogenesis of complex hereditary spastic paraplegia.